The relationship of serum leptin, serum TNF-α, plasma lipids and obesity parameters in patients treated with weight neutral antidepressants - Gangavaram, Naveen Kumar Reddy; Siddapa, Adarsh Lakkur; Muthiah, Bhanukumar; Ram, Dushad (International Journal of Research in Medical Sciences, 2018)
Background: Leptin and tumor necrosis factor (TNFα) are involved in weight regulation1. Elevated lipids are frequently encountered in obese people which are helpful in the formation of atherosclerotic plaques in the coronary arteries. This study helps us to know whether weight neutral antidepressant therapy can be therapeutic option in those with obesity associated with depression. Methods: It is a Longitudinal study of sample size 72 where Patients with obesity attending to JSS hospital who are found to be depressive in both inpatients and out patients fulfilling the inclusion and exclusion criteria. Results: Our study showed mean difference value of weight, BMI and waist circumference, S. leptin, S.TNF-α, S. total cholesterol, S. LDL-C, S. VLDL-C, triglycerides of obese patients treated with lifestyle modifications, psychotherapy and weight neutral antidepressants at baseline and 3rd month was significantly decreased when compared to obese patients treated with lifestyle modifications, psychotherapy alone at baseline and 3rd month is 3.5kgs, 1.2kg/m2, 0.89cm, 9.53pg/ml, 10.86pg/ml, 22.34mg/dl, 17.94mg/dl, 4.42mg/dl, 21.78mg/dl and 1.2kgs, 0.32kg/m2, 0.02cm, 5.22pg/ml, 7.86pg/ml, 11.72mg/dl, 15.37mg/dl, 1.98mg/dl, 9.54mg/dl respectively (p=0.0001). Conclusions: Our study demonstrated a significant weight loss, and significant decrease in S. Leptin, S. TNF- α, TC, LDL-C, VLDL-C, triglycerides, when obese patients treated with lifestyle modifications, psychotherapy and weight neutral antidepressant (Desvenlafaxine).